2004
DOI: 10.1007/s00330-004-2548-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung MRI at 3.0 T: a comparison of helical CT and high-field MRI in the detection of diffuse lung disease

Abstract: The purpose of this study was to evaluate the feasibility of high-field magnetic resonance imaging (MRI) of the lung using a T2-weighted fast-spin echo (TSE) sequence. Comparison was made with helical computed tomography CT findings in patients with diffuse pulmonary diseases. Prospective segment-wise analysis of high-field MR imaging findings in 15 patients with diffuse pulmonary diseases was made using helical CT and HRCT as the standard of reference. The MR studies were performed on a 3.0-T whole body syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 16 publications
4
43
0
1
Order By: Relevance
“…MR imaging at 3.0 T allows high spatial resolution imaging of the pelvis which may be useful in assessing gynecological tumors [4]. Promising results have also been reported for 3.0 T MR imaging in assessing diffuse lung diseases [7], and there is evidence that an increased diagnostic value of cardiac imaging may also expected from MR imaging at 3.0 T [6]. Regarding the musculoskeletal disorders several studies [8][9][10][11] have demonstrated improved imaging quality and speed in imaging of musculoskeletal disorders at 3.0 T and provided preliminary evidence for concomitant improvement in diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…MR imaging at 3.0 T allows high spatial resolution imaging of the pelvis which may be useful in assessing gynecological tumors [4]. Promising results have also been reported for 3.0 T MR imaging in assessing diffuse lung diseases [7], and there is evidence that an increased diagnostic value of cardiac imaging may also expected from MR imaging at 3.0 T [6]. Regarding the musculoskeletal disorders several studies [8][9][10][11] have demonstrated improved imaging quality and speed in imaging of musculoskeletal disorders at 3.0 T and provided preliminary evidence for concomitant improvement in diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 80%
“…Although 3.0 T MR systems are used particularly for neuroradiological applications, several studies [4][5][6][7] have demonstrated the advantages of imaging at a higher magnetic field strength in different areas of body MR imaging. MR imaging at 3.0 T allows high spatial resolution imaging of the pelvis which may be useful in assessing gynecological tumors [4].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple air-tissue interfaces result in large local magnetic gradients that cause intravoxel phase dispersion [24,25]. This makes lung MRI even more challenging at 3 T. Nevertheless, recent studies have shown the feasibility of MRI at 3 T to detect diffuse lung disease [19,26] and the increasing availability of 3-T MR systems in clinical routine (in some cases as alternative to 1.5 T) necessitates optimization of protocols for (dynamic) lung MRI (Table 8). …”
Section: Discussionmentioning
confidence: 98%
“…Therefore, dynamic sequences have been included into recommendations for standard MRI protocols of the lung with 1.5-T systems [6]. Initial results for non-dynamic lung MRI at 3 T are also described [19]. So far, the established FLASH 2D sequences provide a high temporal resolution (eight to nine acquisitions per second), but with an unsatisfying signal and parenchymal contrast.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] MRI at this field strength allows us to double the SNR, which is fundamental in the quality of the final image. The signal determines the brightness of each image pixel and is proportional to the radio frequency (RF) emitted by the tissue.…”
Section: Discussionmentioning
confidence: 99%